MOTHER'S KNOWLEDGE ABOUT TEPID WATER SPONGE COMPRESS THERAPY AT PUSKESMAS CANDI SIDOARJO - Maulana, Hafid; Loetfia Dwi Rahariyani (Global Ten Public Health and Nursing Journal, 2023)
Knowledge and experience of a mother is needed to deal with a problem or disease in children, before the occurrence of an illness, Treatment of fever in children is very dependent on the role of parents, especially mothers. The research design used was a descriptive survey. The population in this study was all mothers who had children under five who lived in the temple in Sugihwaras Village, Sidoarjo Temple as many as 40 people. The results of the study found that most of the people were less knowledgeable 24 people (60%) and a small number of others were well knowledgeable 6 people (15%). Of the 40 respondents of mothers with toddlers in Sugihwaras Village, Candi District, Sidoarjo Regency, most respondents never received information about giving tepid water sponge compress therapy to reduce children's fever, namely 25 people (62.5%) and a small number of others had received information. Of the 15 respondents who had received information about Tepid Water Sponge compress therapy, each received information from health workers, electronic media, friends / neighbors with a percentage of 33.3%. The data analysis used in this study was by using descriptive data analysis. It can be concluded that most of the mother's knowledge about giving Tepid Water Sponge compresses to children under five has less knowledge and most mothers under five lack information about giving Tepid Water Sponge compress therapy.